The effects of parental attachment on personality traits - Yahya, Fatahyah; Nahar, Mohd Imamuddin; Talib, Ahmad Tarmizi; Darshan Singh, Sarjit Singh; Mohad, Abd Hakim; Mohd Isa, Nur Ayuni; Ahmad Khiri, Muhammad Jazlan (Unimas, 2021)
This study aims to identify parental attachment's effects on trainee counsellors' personality traits in the Universiti of Malaysia Sarawak UNIMAS. This research adopted a correlational research design. The respondents were 209 trainee counsellors from the Counselling Program, Universiti Malaysia Sarawak UNIMAS. Two questionnaires were used in this study: The Inventory of Parents and Peer Attachment (IPPA) and the Big Five Personality. The findings indicated a significant relationship between Parents Communication, Attachment and Extraversion and the Agreeableness Trait of Personality. It also showed a significant relationship between Parents Communication Attachment and Extraversion, Agreeableness and Conscientiousness. We also found a significant relationship between Parents' Alienation Attachment and Conscientiousness, Neuroticism and Openness. The study informs society about the need to increase awareness about the importance of knowing attachment styles and personality traits as both impact individuals' lives.